2023
DOI: 10.1039/d3ra00143a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and characterization of magnesium and manganese mixed oxides for the efficient removal of tartrazine dye from aqueous media

Abstract: Nanomaterials are the most effective class of substances for use as adsorbents in wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Figure 5A-C illustrates the nitrogen adsorption/desorption curves of the KE, KE500, and KE700 products, respectively. Furthermore, the obtained findings confirmed that the isotherms correspond to the IV-type isotherm, which shows the mesoporous nature of the products [16]. The surface textures, for example, BET surface area, average pore size, and total pore volume, are listed in Table 2.…”
Section: Nitrogen Adsorption/desorptionsupporting
confidence: 71%
See 3 more Smart Citations
“…Figure 5A-C illustrates the nitrogen adsorption/desorption curves of the KE, KE500, and KE700 products, respectively. Furthermore, the obtained findings confirmed that the isotherms correspond to the IV-type isotherm, which shows the mesoporous nature of the products [16]. The surface textures, for example, BET surface area, average pore size, and total pore volume, are listed in Table 2.…”
Section: Nitrogen Adsorption/desorptionsupporting
confidence: 71%
“…If pH < pHPZC, the medium works to surround the surface of the KE, KE500, and KE700 adsorbents with positive hydrogen ions that are repellent with positively charged BFD dye, as displayed in Scheme 1, and hence reduce the uptake efficacy and uptake capability [16]. If pH > pHPZC, the medium works to surround the surface of the KE, KE500, and KE700 adsorbents with negative hydroxide ions that a ract the positively charged BFD dye, as displayed in Scheme 1, and hence enhance the uptake efficacy and uptake capability [16]. In order to study the stability of the KE, KE500, and KE700 samples at different pH values (2.5-8.5), the XRD of the synthesized adsorbents was carried out at these pH values (figures omi ed for brevity).…”
Section: Effect Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Ren et al synthesized electrospun fiber of BaTiO 3 /ZnO heterostructures using a combination of hydrothermal and electrospinning processes, and photocatalytic activities were investigated by the degradation of methyl orange dye [ 54 ]. The Pechini sol–gel process is a versatile and commonly used technique for the synthesis of a diverse range of nanomaterials such as Mn 0.5 Zn 0.5 Fe 2 O 4 /Fe 2 O 3 , MgMn 2 O 4 /Mn 2 O 3 , Fe 0.5 Mn 0.5 Co 2 O 4 /Fe 2 O 3 , MgMn 2 O 4 /Mn 2 O 3 /Mg 6 MnO 8 , and MgFe 2 O 4 [ 46 , 55 , 56 ]. In this work, barium titanate (BaTiO 3 ) nanoparticles with low crystallite sizes and different morphologies were facilely synthesized using the Pechini sol–gel technique.…”
Section: Introductionmentioning
confidence: 99%